Inovasi Kurikulum Pendidikan SMA Darul Ulum 2 di Pondok Pesantren Darul Ulum Jombang - Hakim, Muhammad Nur; Hasan, Mohammad Tholhah (STIT Pringsewu, 2019)
ABSTRACTIn this era of globalization the government has focused on pesantren to advance the quality of education in Indonesia. The development of pesantren education must be carried out competitively. Pesantren education must also be able to provide a guarantee of the superiority of competent outputs. The development carried out by Islamic boarding schools is an effort to produce superior outputs and outflows.This study aims to determine the innovations created by pesantren through schools by referring to the following formulation: 1) school curriculum innovation. 2) the implications of school curriculum innovations on boarding schools, and 3) the relevance of school curriculum innovations to boarding schools.The results of the study show that: First, the curriculum innovation process is carried out through five stages, namely 1) the formulation stage by introducing the pesantren education model, 2) the stage of adjustment, the Cambridge curriculum is adjusted to the existing system, 3) the determination stage by establishing an international curriculum adoption , 4) the stage of support, namely taking action to support innovation, 5) the stage of correction, which is a form of correction of the program implemented. Second, the implications of the educational curriculum innovation in the school on the pesantren curriculum are found in the curriculum component which includes: 1) curriculum content; 2) learning media; 3) learning strategies and learning processes; and 4) evaluation; Third, school curriculum innovation is closely related, relevant, suitable and connected with the pesantren curriculum in the form of both the school curriculum and the boarding curriculum.